Mitochondrial modulators of hypoxia-related pathways in tumours - Snell, CE (2013)
The Lon protease is a mitochondrial matrix quality-control protease belonging to the family of AAA+ proteins (ATPases associated with many cellular activities). We had previously found Lon to be upregulated in lung tumours with a non-angiogenic phenotype in a microarray study comparing these to conventional angiogenic tumours. In this project I set out to investigate whether Lon had any role in modulating the hypoxic response of tumour cells. Using a novel monoclonal antibody against Lon, I found that upregulation of Lon was present in breast and lung tumours and that higher levels of Lon are correlated with shorter overall survival in breast cancer patients. Targeting Lon with siRNA and shRNA in tumour cell lines reduced the normoxic and hypoxic stabilisation of HIF-α subunits. This is mediated through a mechanism independent of the activity of HIF-prolyl hydroxylases and independent of any changes in mitochondrial transcription. I found that the pre-imported form of Lon could bind and chaperone VHL in the cytoplasm potentially modulating VHL activity. In cell lines and human tumours, I observed that the proline-hydroxylated form of HIF-1α is induced by hypoxia and the hydroxylated form of HIF-1α is associated with shorter overall survival in breast cancer patients. This observation supports the notion that higher levels of Lon is associated with poor survival by downregulating VHL leading to higher levels of hydroxylated HIF. Finally I show that targeting Lon in cell lines is able to inhibit growth in a cell-line dependent fashion and partially reverses the Warburg effect, increasing oxygen consumption and reducing lactate production. In conclusion, I have demonstrated the broad therapeutic potential of targeting the Lon protease in tumours and highlighted a mechanism of post-hydroxylation HIF-regulation that has not been previously recognised in VHL competent tumours.